Efektivitas dan Praktikalitas Buku Ajar Berbasis Problem-Based Learning dalam Meningkatkan Pemahaman Analisis Laporan Keuangan Mahasiswa - Agustin, Alvy Yuli (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study aims to develop a Problem-Based Learning (PBL)-based textbook to enhance students' understanding in the Financial Statement Analysis course. The research employed a quantitative approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The validity, practicality, and effectiveness of the teaching materials were evaluated through statistical tests using questionnaires and learning outcome tests. The results indicate that the developed PBL-based textbook has high validity, with significant Pearson correlation values across all validity indicators. The practicality of the textbook was rated as adequate by students, although certain aspects require improvement. The effectiveness of the textbook is evident from the significant improvement in students' learning outcomes, demonstrating that the PBL-based approach enhances analytical and critical thinking skills. This study concludes that the PBL-based teaching material is effective and relevant for use in Financial Statement Analysis courses, while also supporting the development of skills applicable to the professional world.